A sisters' story: comparative phylogeography and taxonomy of Hierophis viridiflavus and H. gemonensis (Serpentes, Colubridae). (15th April 2015) - Mezzasalma, Marcello; Dall'Asta, Andrea; Loy, Anna; Cheylan, Marc; Lymberakis, Petros; Zuffi, Marco A. L.; Tomović, Ljiljana; Odierna, Gaetano; Guarino, Fabio M.
<x xml:space="preserve">Abstract</x> We used a multidisciplinary approach to infer the taxonomy and historical biogeography of Hierophis viridiflavus and H. gemonensis, performing molecular analyses of mitochondrial (16S, Cyt‐b, ND4) and nuclear markers (PRLR), a landmark‐based morphometric study and a cytogenetic analysis. Our data distinguished three main groups in the studied species, corresponding to H. gemonensis and to two monophyletic clades (E and W) within H. viridiflavus. Clades E and W display a significant genetic (about 4% for Cyt‐b and ND4) and morphological divergence and a different morphology of the W sex chromosome (submetacentric in clade E and telocentric in clade W). Taking into account the existing divergence, these clades appear to represent independent phylogenetic units, deserving elevation to species status. Specific names should be H. viridiflavus (Lacépède, 1789) and H. carbonarius (Bonaparte 1833) for clades W and E, respectively. The phylogeography of the studied species is only partially concordant with a general pattern of 'southern richness and northern purity' of genetic diversity, whereas H. gemonensis exhibits high genetic diversity at low latitudes (especially in the Peloponnese), H. carbonarius shows a number of different haplotypes both at low (along the southern Italian Apennines and in Sicily) and high latitudes in Italy. Furthermore, a relaxed clock model hypothesizes the differentiation between H. gemonensis and H. viridiflavus sensu lato at about 7 Mya, in the Messinian. Subsequently, the speciation involving H. viridiflavus sensu stricto and H. carbonarius took place in the Quaternary, probably as a result of Pleistocene climatic oscillations. Furthermore, our results are consistent with the existence of several 'refugia within refugia' in Italy and in the Balkans and depict the major cladogenesis as allopatric events, mainly driven by paleoclimatic and geographical factors.